The knowledge management toolkit practical techniques for building a knowledge management system - Tiwana, Amrit, 1974- (Upper Saddle River, NJ Prentice Hall PTR, 2000)
"The Knowledge Management Toolkit delivers hands-on techniques and tools for making KM happen at your company. You'll learn exactly how to use KM to make sure that every key decision is fully informed as you build on your existing intranet, data warehouse, and project management investments. Top researcher Amrit Tiwana walks you through the development of an enterprise KM system from start to finish, showing how every stage can serve as a foundation for later enhancements."--BOOK JACKET.
Keywords: Knowledge management